2018
DOI: 10.1590/1678-992x-2016-0363
|View full text |Cite
|
Sign up to set email alerts
|

Empirical models to predict feed intake of growing-finishing pigs reared under high environmental temperatures

Abstract: Several empirical models were proposed to predict feed intake (FI) of growingfinishing pigs reared under high environmental temperatures. However, these models have not been evaluated under conditions different from those in which they were developed. Twelve empirical models were evaluated using a database built after systematic literature review (observed data: 28 studies in which the FI was evaluated in pigs under high environmental temperatures). Model accuracy was assessed using the mean squared of predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For FI after 21 d, the accuracy of the model (Equation 5) was limited by the ER, however, this error is systematic and can be corrected by further modeling procedures. However, the accuracy observed for body weight gain estimation after 21 d (Equation 11) was limited by ED, which is a random error, difficult to correct ( Perondi et al., 2018 ). The diversity in the studies that composed the databases may contribute to this higher ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For FI after 21 d, the accuracy of the model (Equation 5) was limited by the ER, however, this error is systematic and can be corrected by further modeling procedures. However, the accuracy observed for body weight gain estimation after 21 d (Equation 11) was limited by ED, which is a random error, difficult to correct ( Perondi et al., 2018 ). The diversity in the studies that composed the databases may contribute to this higher ED.…”
Section: Discussionmentioning
confidence: 99%
“…The MSPE was then broken down into error of central tendency ( ECT ) and error of regression ( ER ), which together with ECT indicated the lack of trueness, and error due to disturbances ( ED ) which indicated the lack of precision, following the proposition described by Theil (1966) . Afterward, the interpretation was performed according to Perondi et al. (2018) .…”
Section: Methodsmentioning
confidence: 99%
“…Compared with many studies (Zhao et al, 2006;Yan et al, 2010;Peng et al, 2014;Yan et al, 2016;Yan et al, 2017;Qiu et al, 2017;Liu et al, 2018), the current research determined the optimum potential intensive pig farms considering the suitability evaluation result of the spatial layout of intensive pig farms average surface temperature and area index results of cultivated land spatial matched with intensive pig farm. Furthermore, the existing research results had shown that the high temperature environment had a profound impact on the pig industry (Xia et al, 2016;Perondi et al, 2018;Morales et al, 2019;Oliveira et al, 2019). Therefore, selecting the region with relatively low temperature in summer as the potential location for spatial layout planning of intensive pig farms is highly valuable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results showed that the high temperature environment had a strong influence on the pig industry (Oliveira et al,2019). With the increase in the environment temperature, the thermoregulation indices of pig such as food intake, evaporation and heat dissipation, respiratory rate, and so on, have changed dramatically (Xia et al, 2016;Perondi et al, 2018;Morales et al,2019;Oliveira et al,2019). However, few studies examined the spatial layout of intensive pig farms considering the current regional environment temperature.…”
Section: Introductionmentioning
confidence: 99%
“…When a prediction needs to be made on the likely behavior of an animal, such as the feed intake of a sow or, in this case, the likelihood of a TB event, empirical modeling may be more suitable. Empirical modelling uses assumptions made to input variables to generate predictions [18], which is why it requires large amounts of data to determine these assumptions. For this type of DST to be reliable, one would expect the data to be sourced from a large range of appropriate parameters to ensure the risk assessments are true to the situation.…”
Section: Introductionmentioning
confidence: 99%